2015
DOI: 10.17221/8460-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between growth and body condition development during the rearing period and performance in the first three lactations in Holstein cows

Abstract: ABSTRACT:The relationship between growth and development of body condition during the rearing of replacement heifers and their subsequent performance in the production period of Holstein cows in the Czech Republic was studied. The data set used in this study covered 733 Holstein heifers born on one farm during the years [2004][2005][2006][2007][2008][2009]. The evaluated effects considered were body weight (BW), average daily gain of live weight (ADG), and body condition score (BCS) of heifers. The results dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Additionally, housing automatically fed calves in small groups (6–9 calves) was associated with a higher growth rate (0.022 cm/day, about 40 g/day, p < 0.05) compared to calves housed in larger groups (12-18 calves; Svensson and Liberg [ 114 ]). In turn, the higher the average daily gain (ADG) of weight in different ages before the first calving, the younger ( p < 0.05) the AFC [ 115 ]. In pasture-based dairy herds, Chuck et al [ 116 ] reported a positive association ( p < 0.05) between ADG from 1 month of age to first breeding on cumulative milk, fat, and protein yield at 100 and 250 days in milk in primiparous.…”
Section: How Can We Improve Dairy Cow Longevity?mentioning
confidence: 99%
“…Additionally, housing automatically fed calves in small groups (6–9 calves) was associated with a higher growth rate (0.022 cm/day, about 40 g/day, p < 0.05) compared to calves housed in larger groups (12-18 calves; Svensson and Liberg [ 114 ]). In turn, the higher the average daily gain (ADG) of weight in different ages before the first calving, the younger ( p < 0.05) the AFC [ 115 ]. In pasture-based dairy herds, Chuck et al [ 116 ] reported a positive association ( p < 0.05) between ADG from 1 month of age to first breeding on cumulative milk, fat, and protein yield at 100 and 250 days in milk in primiparous.…”
Section: How Can We Improve Dairy Cow Longevity?mentioning
confidence: 99%
“…Brickell et al (2007) reported that cows with a higher BW at 6 mo old (183 kg; SD = 36 kg) had an age at first calving lower than 23 mo compared with animals with a lower BW at at 6 mo old (162 kg; SD = 35 kg). Additionally, a positive relationship was reported between first-lactation milk yield and the ADG from weaning to first service (Svensson and Hultgren, 2008) or conception (Vacek et al, 2015) as well as between the ADG during the first 2 mo of life and completing the first lactation (Bach, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…The occurrences of health problems before the first calving were reported to negatively affect milk production (Svensson and Hultgren, 2008) and reproduction (Hultgren and Svensson, 2010) of dairy cows. In addition, a high ADG from birth to weaning was associated with early age at first calving (Vacek et al, 2015), high milk yield in the first lactation (Svensson and Hultgren, 2008;Vacek et al, 2015), and low occurrence of veterinarian-treated cases of mastitis at the beginning of the lactation of primiparous cows (Svensson et al, 2006). Because failure to reproduce, incidence of health issues such as mastitis and feet and leg problems, and low milk production are the main reported reasons for culling in high milk-producing countries (Dallago et al, 2021), altogether these studies provide evidence that early life conditions-especially during the rearing period-have an adverse effect on cow longevity.…”
Section: Introductionmentioning
confidence: 98%